Applying a chemical equilibrium model for optimizing struvite precipitation for ammonium recovery from anaerobic digester effluent. (20th March 2017) - Jia, Guangan; Zhang, Hu; Krampe, Joerg; Muster, Tim; Gao, Baoyu; Zhu, Nanwen; Jin, Bo
Abstract: Ammonium (NH4 + ) removal and recovery from wastewater by struvite precipitation is a sustainable approach, generating valuable fertilizer and reducing environmental impact. This study applied a chemical equilibrium model-Visual MINTEQ to optimise the systematic operation parameters for struvite precipitation from anaerobic digester effluent in a wastewater treatment plant. Designed systematic parameters were used as inputs into the model with different molar ratios of magnesium (Mg 2+ )/phosphate (PO4 3− ) and pH control approach. The results show that the Mg 2+ /PO4 3− molar ratio can significantly affect the NH4 + recovery efficiency, and over 96% NH4 + recovery was obtained at an Mg 2+ /PO4 3− ratio of 2:1. The experimental results corresponded well with the model outputs in terms of ammonium recovery efficiency, struvite crystal formation and alkaline dosages; indicating that this model can be applied to predict precipitation process in order to enhance ammonium recovery efficiency and struvite formation. The economic benefit was briefly analyzed considering chemical costs. Our results indicate that ammonium removal and recovery from waste streams by struvite precipitation is a sustainable approach, generating valuable fertilizer and reducing nutrient contaminant loading in the eco-system. Highlights: Producing valuable fertilizer from anaerobic digestion effluent for activate sludge treatment. MINTEQ 3.0 is a useful software program for optimizing struvite precipitation. XRD and SEM analyses confirm that the ammonium was recovered to form struvite. Ammonium recovery via struvite precipitation is economically viable.